2007
DOI: 10.2337/db06-1242
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperglycemia Induces a Global Downregulation of Gene Expression in Adipose Tissue and Skeletal Muscle of Healthy Subjects

Abstract: To define the effects of acute hyperglycemia per se (i.e., without the confounding effect of hyperinsulinemia) in human tissues in vivo, we performed global gene expression analysis using microarrays in vastus lateralis muscle and subcutaneous abdominal adipose tissue of seven healthy men during a hyperglycemic-euinsulinemic clamp with infusion of somatostatin to inhibit endogenous insulin release. We found that doubling fasting blood glucose values while maintaining plasma insulin in the fasting range modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 37 publications
3
56
1
Order By: Relevance
“…PDK4 gene expression has previously been suppressed when using a hyperinsulinemic-euglycemic clamp in rats [18] and a hyperglycemic-euinsulinemic clamp in humans [19]. In the present study, we observed that PDK4 gene expression was downregulated at 120 min in all test meals except for the WAT.…”
Section: Discussionsupporting
confidence: 69%
“…PDK4 gene expression has previously been suppressed when using a hyperinsulinemic-euglycemic clamp in rats [18] and a hyperglycemic-euinsulinemic clamp in humans [19]. In the present study, we observed that PDK4 gene expression was downregulated at 120 min in all test meals except for the WAT.…”
Section: Discussionsupporting
confidence: 69%
“…As preliminarily reported, another possible explanation is that in oscillating glucose conditions the cells are not able in sufficiently increase their own intracellular antioxidant defenses (29), a condition which has been suggested to favor the development of diabetes complications (30 -31). In this regard, a recent study showed that during acute hyperglycemia, in normal subjects, several genes involved in free radical detoxification were downregulated (32).…”
Section: Diabetes Vol 57 May 2008mentioning
confidence: 99%
“…Thus, in males, increased expression of genes associated with mitochondrial energy production was accompanied by increased expression of genes associated with reduction of reactive oxygen species and inflammation. One of the potential negative effects of hyperglycemia associated with diabetes is damage to cells from oxidative stress (Brownlee 2005;Meugnier et al, 2007), indicating that hepatic sexual dimorphism should be considered when using the zebrafish as a model in studies of abnormal states of glucose homeostasis.…”
Section: Sexual Dimorphism Of the Hepatic Transcriptomementioning
confidence: 99%